2014
DOI: 10.1007/s10336-014-1082-4
|View full text |Cite
|
Sign up to set email alerts
|

Male territories and the lek-like mating system of MacQueen’s Bustard Chlamydotis macqueenii

Abstract: Lekking is a promiscuous breeding system in which females visit groups of displaying males only for the purpose of mating. The spatial organization of these groups can range from tight aggregations of individuals, or leks, to loose clusters of males displaying on exploded-leks, and it can also include males seemingly displaying alone. As the distance between displaying males increases, it becomes possible for them to hold fixed territories and for females to select mates not for their genetic quality, as on tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The Asian houbara Chlamydotis macqueenii (hereafter 'houbara') is a medium-sized bustard species adapted to arid and semi-arid ecosystems (Hoyo et al 1996, Van Heezik & Seddon 1999, Riou & Combreau 2014. It is resident in the southern extent of its range (from the Arabian Peninsula to southern Central Asia), but migratory in most of Central Asia and parts of Eastern Asia (Goriup 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The Asian houbara Chlamydotis macqueenii (hereafter 'houbara') is a medium-sized bustard species adapted to arid and semi-arid ecosystems (Hoyo et al 1996, Van Heezik & Seddon 1999, Riou & Combreau 2014. It is resident in the southern extent of its range (from the Arabian Peninsula to southern Central Asia), but migratory in most of Central Asia and parts of Eastern Asia (Goriup 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This is a hard feat, because collecting data on large leks is technically difficult 18 . Recent studies of the spatial organization of MacQueen’s Bustard ( Chlamydotis macqueenii ) have shown that individuals organize into ‘exploded’ leks where the typical distance between individual display sites becomes of the order of 1 km and males tend to hold fixed territories 19 . This feature allows a reliable determination of the spatial distribution of display sites by using GPS and radio-tracking in combination with direct observation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…
Figure 3 Comparison between the distribution of the number of nearest neighbors in a real population of MacQueens Bustard and in our model. ( a ) Spatial distribution of the display sites in the exploded lek of a population of MacQueen’s Bustard 19 . White circles represent radio-tagged individuals, black circles non-tagged individuals and dots undetermined observations.
…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations